The Distribution of Genes Associated With Regulated Cell Death Is Decoupled From the Mitochondrial Phenotypes Within Unicellular Eukaryotic Hosts - Teulière, Jérôme; Bernard, Guillaume; Bapteste, Eric (Frontiers in Cell and Developmental Biology, 2020)
Genetically regulated cell death (RCD) occurs in all domains of life. In eukaryotes, the evolutionary origin of the mitochondrion and of certain forms of RCD, in particular apoptosis, are thought to coincide, suggesting a central general role for mitochondria in cellular suicide. We tested this mitochondrial centrality hypothesis across a dataset of 67 species of protists, presenting 5 classes of mitochondrial phenotypes, including functional mitochondria, metabolically diversified mitochondria, functionally reduced mitochondria (Mitochondrion Related Organelle or MRO) and even complete absence of mitochondria. We investigated the distribution of genes associated with various forms of RCD. No homologs for described mammalian regulators of regulated necrosis could be identified in our set of 67 unicellular taxa. Protists with MRO and the secondarily amitochondriate Monocercomonoides exilis display heterogeneous reductions of apoptosis gene sets with respect to typical mitochondriate protists. Remarkably, despite the total lack of mitochondria in M. exilis, apoptosis-associated genes could still be identified. These same species of protists with MRO and M. exilis harbored non-reduced autophagic cell death gene sets. Moreover, transiently multicellular protist taxa appeared enriched in apoptotic and autophagy associated genes compared to free-living protists. This analysis suggests that genes associated with apoptosis in animals and the presence of the mitochondria are significant yet non-essential biological components for RCD in protists. More generally, our results support the hypothesis of a selection for RCD, including both apoptosis and autophagy, as a developmental mechanism linked to multicellularity.